Improving Public Health through Exercise for Quality of Life: An Overview in an Implementation Perspective Sport for Development and Peace - Roring, Lucky Angkawidjaja; Ma'mun, Amung (ASEAN Journal of Sport for Development and Peace, 2024)
The article aims to produce a recommendation formulation of efforts to improve public health through sports to gain a quality of life based on the results of a review of the implementation of Sport for Development and Peace in five countries, namely India, Uganda, Canada, Azerbaijan and Australia. The method used is a literature review of several written documents, research results and publications related to the topic of study. The focus of the study includes four indicators, namely: integration, cooperation, direction, and feasibility. The results of the study show: 1) on the integration indicator, the programs developed by the five countries have become an integrated and integral part of their respective peace-building or community development programs; 2) in the aspect of cooperation, there has been the involvement of local public figures and sports figures as a form of support and local legitimacy; 3) in the aspect of direction, the developed sports program is supervised by people and institutions that have the authority to conduct supervision; and 4) in the feasibility aspect,Based on the results of the study, it is recommended that the government initiate the implementation of Sport for Development and Peace by taking into account the four indicators studied and adjusting to the conditions and development of sports policies.